Competencias socioafectivas vinculadas al trabajo en equipo - Segaspini Peixoto, Eurídice (2025)
The purpose of this article is to identify socio-affective competencies linked to teamwork that are mobilized in the resolution of problem situations in the Mathematics curriculum. The study was conducted using a qualitative case study approach. The participants were 22 high school students from a public school in southern Brazil. Data were collected through the following instruments: the Competency Wheel, a socio-affective competencies questionnaire, a written teamwork report, and the teacher’s logbook. The results indicate that the socio-affective competencies openness to new experiences and empathy emerged in most teams. In addition, affective bonds and affinity were the main criteria influencing the selection of team members.